2023
DOI: 10.35473/jhhs.v5i1.151
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-faktor yang Mempengaruhi Sikap Perawat dalam Keselamatan Pasien: Systematic Review

Abstract: Nurses have a critical role in ensuring care delivery focuses on patient safety and injury prevention during treatment. Positive attitudes toward injury prevention can improve patient safety; however, several factors such as age and work experience are believed to have influenced nurses’ safety attitudes. A systematic review searched data through online databases such as Scopus, ScienceDirect, Wiley Online Library, and EBSCO for articles published between 2010 and 2020. The keywords used were "patient safety a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Safety attitude itself relates to how nurses implement safety (Galleryzki et al, 2021). Knowledge received by nurses affects nurses' safety attitudes (Galleryzki, 2023). Research conducted in several hospitals in Indonesia showed an average implementation score of Patient Safety Goals (PSG) of 159.03 (85.4%).…”
Section: Introductionmentioning
confidence: 99%
“…Safety attitude itself relates to how nurses implement safety (Galleryzki et al, 2021). Knowledge received by nurses affects nurses' safety attitudes (Galleryzki, 2023). Research conducted in several hospitals in Indonesia showed an average implementation score of Patient Safety Goals (PSG) of 159.03 (85.4%).…”
Section: Introductionmentioning
confidence: 99%